Pengaruh Pemangkasan Cabang Lateral terhadap Hasil dan Mutu Benih Kacang Panjang (Vigna sinensis L.) - HANDAYANI, LILIK; RAKA, I GUSTI NGURAH; ASTININGSIH, ANAK AGUNG MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Effect of Lateral Branch Trimming Against Results and Quality of Long Bean Seeds (Vigna sinensis L.) Long beans include shabby legume-shaped families that sprout or spread and are able to bind free nitrogen from the air through symbiosis with rhizobium bacteria. Long bean plant is an indeterminate type of plant that is vegetative phase that continues to be active even though it has entered the generative phase. Lateral branch in long beans will continue to grow, so that trimming measures are needed so that the competition for the use of assimilate result from photosynthesis can be reduced and can be used fully when the generative phase takes place. This study aims to determine the effect of lateral branch trimming on the yield and quality of long beans seeds. The method used is paired T test system. The treatments tested were trimming of lateral branches and without trimming of lateral branches. Each treatment was repeated 25 times and each replication was represented by 3 plants. Data were analyzed using t-test. The result showed that the treatment of lateral trimming of long bean plants was able to produce higher leaf chlorophyll content compared to those that were not trimmed, the treatment of lateral branch trimming of long bean plants was able to produce seeds of 14,09 tons/ha on the trimmed ones and 5,24 tons/ha on the untrimmed and lateral branch trimming treatment of long bean plants was able to produce 1000 seed weight of 190,65 g which was trimmed and 165,76 g on the non trimmed. Thus it was also able increase the germination capacity by 92% in the trimmed one and 87% in the non-trimmed one.